2022
DOI: 10.1108/jeim-09-2021-0396
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of circular supply chains barriers in the era of Industry 4.0 transition using an extended decision-making approach

Abstract: PurposeThe poor leadership style is a key obstacle to the effective implementation of Industry 4.0 technologies. To successfully apply the Industry 4.0 technologies, which can enhance the sustainability of firms, senior management needs to be inspiring and transformational. On the other hand, numerous factors can hinder the Industry 4.0 transition and “Circular Supply Chain (CSC)” transformation. Therefore, the main purpose of this study is to evaluate the related barriers of CSCs in the era of Industry 4.0 tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(23 citation statements)
references
References 85 publications
0
22
0
Order By: Relevance
“…In addition, the results of the study found that the extended approach was effective and efficient in evaluating the sustainability risk factors in supply chain management of the manufacturing firms. Shang et al (2022) assessed circular supply chains barriers in the era of Industry 4.0 transition using an extended decision-making approach. Therefore, this study to evaluate the related barriers of CSCs in the era of Industry 4.0 transition developed an innovative decisionmaking approach with the help of the "Combined Compromise Solution (CoCoSo)" method and "Criteria Importance Through Intercriteria Correlation (CRITIC)" method on the "q-Rung Orthopair Fuzzy Sets (q-ROFSs)."…”
Section: Decision-making and Fuzzy Sets Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the results of the study found that the extended approach was effective and efficient in evaluating the sustainability risk factors in supply chain management of the manufacturing firms. Shang et al (2022) assessed circular supply chains barriers in the era of Industry 4.0 transition using an extended decision-making approach. Therefore, this study to evaluate the related barriers of CSCs in the era of Industry 4.0 transition developed an innovative decisionmaking approach with the help of the "Combined Compromise Solution (CoCoSo)" method and "Criteria Importance Through Intercriteria Correlation (CRITIC)" method on the "q-Rung Orthopair Fuzzy Sets (q-ROFSs)."…”
Section: Decision-making and Fuzzy Sets Methodsmentioning
confidence: 99%
“…Shang et al (2022) assessed circular supply chains barriers in the era of Industry 4.0 transition using an extended decision-making approach. Therefore, this study to evaluate the related barriers of CSCs in the era of Industry 4.0 transition developed an innovative decision-making approach with the help of the “Combined Compromise Solution (CoCoSo)” method and “Criteria Importance Through Intercriteria Correlation (CRITIC)” method on the “q-Rung Orthopair Fuzzy Sets (q-ROFSs).” CRITIC in this combined method was used to predict the importance or weighting degrees of the CSCs barriers in the age of Industry 4.0 transition.…”
Section: Article Classificationsmentioning
confidence: 99%
“…The shift to CE is being driven by consumers and private and public agencies (European Commission, 2015) but remains constrained by cultural, regulatory, market and technological factors (Kirchherr et al, 2018). It is argued that the transformation of businesses toward CE will create value through clean production, closed-loop systems, reverse logistics, eco-design and product life cycle management (Shang et al, 2022). Countries have embraced CE as an efficiency-oriented new development model that is much broader than the narrow waste recycling approach.…”
Section: Introductionmentioning
confidence: 99%
“…, 2018). It is argued that the transformation of businesses toward CE will create value through clean production, closed-loop systems, reverse logistics, eco-design and product life cycle management (Shang et al. , 2022).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation